The internal pressure and stress environment of the scoliotic intervertebral disc--a review. - Meir, A; McNally, D; Fairbank, J; Jones, D; Urban, J (2008)
The aetiology, in terms of both initiation and progression, of the deformity in idiopathic scoliosis is at present unclear. Even in neuromuscular cases, the mechanisms underlying progression are not fully elucidated. It is thought, however, that asymmetrical loading is involved in the progression of the disease, with evidence mainly from animal studies and modelling. There is, however, very little direct information as to the origin or mechanism of action of these forces in the scoliotic spine. This review describes the concept of intervertebral disc pressure or stress and examines possible measurement techniques. The biological and mechanical consequences of abnormalities in these parameters are described. Future possible studies and their clinical significance are also briefly discussed. Techniques of pressure measurement have culminated in the development of 'pressure profilometry', which provides stress profiles across the disc in mutually perpendicular axes. A hydrated intervertebral disc exhibits mainly hydrostatic behaviour. However, in pathological states such as degeneration and scoliosis, non-hydrostatic behaviour predominates and annular peaks of stress occur. Recent studies have shown that, in scoliosis, high hydrostatic pressures are seen with asymmetrical stresses from concave to convex sides. These abnormalities could influence both disc and endplate cellular activity directly, causing asymmetrical growth and matrix changes. In addition, disc cells could be influenced via nutritional changes consequent to end-plate calcification. Evidence suggests that the stress environment of the scoliotic disc is abnormal, probably generated by high and asymmetrical loading of non-muscular origin. If present in the scoliotic spine during daily activities, this could generate a positive feedback of cellular changes, resulting in curve progression. Future advances in understanding may rely on the development of computer models owing to the difficulties of in-vivo invasive measurements.